2019
DOI: 10.5093/pi2019a6
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Addiction and Social Support: A Three-year Longitudinal Study

Abstract: For approximately fifty years, scholars have empirically confirmed the benefits of social support for health and well-being. This empirical evidence comes from cross-sectional and longitudinal studies carried out both in the general and at-risk populations (Holt-Lunstad, Smith,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 45 publications
2
26
0
3
Order By: Relevance
“…Only two studies used longitudinal data [64,65], and none of the others conducted follow-up assessments on the cross-sectional analyses of smartphone use and behavior. That is, limitations included: The use of cross-sectional data, which limits the ability to draw causal inferences, especially when determining the direction of association between SA/PSU and risk factors of interest; small sample size; not being able to determine whether study characteristics preceded SA/PSU development or were the outcome of smartphone use; use of less-than-optimal instruments tending to be subjective rather than objective; incentive-influenced survey answers; and attrition.…”
Section: Generalizability Of Study Results and Biasesmentioning
confidence: 99%
“…Only two studies used longitudinal data [64,65], and none of the others conducted follow-up assessments on the cross-sectional analyses of smartphone use and behavior. That is, limitations included: The use of cross-sectional data, which limits the ability to draw causal inferences, especially when determining the direction of association between SA/PSU and risk factors of interest; small sample size; not being able to determine whether study characteristics preceded SA/PSU development or were the outcome of smartphone use; use of less-than-optimal instruments tending to be subjective rather than objective; incentive-influenced survey answers; and attrition.…”
Section: Generalizability Of Study Results and Biasesmentioning
confidence: 99%
“…Data were collected via self-report measures and were cross-sectional, which precludes any causality statement. Recent studies have used a longitudinal design (Herrero, Torres, Vivas, & Urueña, 2019;Lapierre, Zhao, & Custer, 2019;Lee et al, 2020) or a qualitative approach (Yang, Asbury, & Griffiths, 2019) for the study of smartphone use/dependency or PSU, and further studies that use these alternative methodologies should be conducted to complement our approach. The present study focused on a specific demographic group (i.e., college students with regular access to the Internet, predominantly females), thus limiting the generalisability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, as previous research has indicated, parents are not the only influence on adolescent development. In this sense, adolescents may also be influenced by different settings inside and outside the family [107][108][109], including family structure (e.g., single parent, both natural parents, or one natural parent and a step-parent) [110], parental employment [111], peers [112], and school [113]. However, despite these influences, a common pattern between parenting styles, self-esteem and internalization of social was found in the three countries: indulgent parenting (parental warmth without parental strictness) is consistently related to the highest levels of adolescent self-esteem and internalization of social values.…”
Section: Discussionmentioning
confidence: 99%